Trends in Research Related to Ophthalmic OCT Imaging From 2011 to 2020: A Bibliometric Analysis - Yu, Ziyan; Ye, Jie; Lu, Fan; Shen, Meixiao (Frontiers in Medicine, 2022)
Objective The aim of this study was to explore hotspots and global research trends on optical coherence tomography (OCT) in the ophthalmic imaging field using the bibliometric technique. Methods Documents related to OCT in the ophthalmic imaging field between 2011 and 2020 were extracted from the Science Citation Index (SCI) Expanded database. Downloaded raw data were analyzed using the VOSviewer and CiteSpace software. Bibliometric networks, including publication number per year, countries, authors, journals, international collaborations, and keywords were constructed. Results A total of 4,270 peer-reviewed documents were retrieved, and annual research output in the past 10 years has increased significantly. The largest publishing country was the United States, and the most productive journal was Investigative Ophthalmology and Visual Science (IOVS). The most active academic institution was the University of California, Los Angeles, and the top rank publishing author was Duker JS. The most co-cited references mainly focused on new emerging OCT techniques such as spectral domain optical coherence tomography (SD-OCT) and optical coherence tomography angiography (OCTA). Conclusion The bibliometric analysis of development trends on OCT in the ophthalmic imaging field on various aspects could provide developers or researchers with valuable information to propose future research directions and to pursue further cooperation.